LITERATURE REVIEW: PENGARUH PEMBERIAN JUS BUAH NAGA MERAH TERHADAP PENURUNAN KADAR GULA DARAH PADA PASIEN DIABETES MELITUS TIPE ll: LITERATURE REVIEW: PENGARUH PEMBERIAN JUS BUAH NAGA MERAH TERHADAP PENURUNAN KADAR GULA DARAH PADA PASIEN DIABETES MELITUS TIPE ll - Muhamad Daetun; Zahrah Maulidia Septimar (Lembaga Penelitian Sekolah Tinggi Ilmu Kesehatan Kuningan, 2021)
Background: Diabetes mellitus is a non-communicable disease. Diabetes mellitus can be controlled by administering insulin therapy. In addition to insulin therapy controlling blood sugar levels can be done by using dragon fruit. The purpose of this review literature is to determine the effect of giving red dragon fruit juice on reducing blood sugar levels in patients with type II diabetes mellitus in 2020. Research Methods: this research uses the literature study method or literature review, literature studies can be obtained from various sources both journals, books, documentation and literature that is critically reviewing or reviewing the knowledge, ideas or findings contained in a literature. Research Results: the effect of giving dragon fruit juice on reducing blood sugar levels in patients with type II diabetes mellitus conducted by previous studies various health benefits made an herbal drink to reduce blood sugar levels and can be applied by various research subjects such as adolescents, adults and the effective elderly for reducing blood sugar levels can be seen from the decrease in pre-test and post-test scores. Conclusions and Recommendations: Therapy for giving dragon fruit juice can be done anywhere, not only for diabetics, but this dragon fruit has many benefits and can be consumed by teenagers, adults Keywords: dragon fruit, diabetes